2019
DOI: 10.1016/j.smr.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Interorganisational conflict between national and provincial sport organisations within China’s elite sport system: Perspectives from national organisations

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…PSBs are accountable to their respective PGs rather than the GAS because PSBs are funded mainly by PGs. The interorganizational conflict between PSBs and the GAS and the governance instrument role that the National Games of China play have been carefully examined by Zheng et al [13]. A more detailed clarification would exceed the scope of this article.…”
Section: Elite Sport Training In China and An Integrative Model Of Organizational Change In Sport 21 Institutional Analyses On Chinese Elmentioning
confidence: 97%
See 2 more Smart Citations
“…PSBs are accountable to their respective PGs rather than the GAS because PSBs are funded mainly by PGs. The interorganizational conflict between PSBs and the GAS and the governance instrument role that the National Games of China play have been carefully examined by Zheng et al [13]. A more detailed clarification would exceed the scope of this article.…”
Section: Elite Sport Training In China and An Integrative Model Of Organizational Change In Sport 21 Institutional Analyses On Chinese Elmentioning
confidence: 97%
“…These studies are commonly termed institutional analyses [7,16]. More recently, Zheng et al [13] concluded that the PRC enjoys a well-organized and stratified three-level training system (see Figure 1). Officially established in 1963, when the then Sports Ministry promulgated the Regulations of Outstanding Athletes and Teams [12] (p. 516), it was recognized as one of the most effective training systems in the world and perceived as the core of Juguo Tizhi (precisely and explicitly interpreted as "whole country support for elite sport system"), underpinning the PRC's continuous presence as one of the three best-performing nations at the Summer Olympics [5,10,17].…”
Section: Elite Sport Training In China and An Integrative Model Of Organizational Change In Sport 21 Institutional Analyses On Chinese Elmentioning
confidence: 99%
See 1 more Smart Citation
“…The change management process has posed challenges for sport managers because the majority of change initiatives fail (Cunningham, 2006b). Amongst the various reasons that have been identified to explain the failure, or unintended consequences of organizational change are the timing of change (Saxton, 1995), institutional resistance (Kikulis, 2000;Kikulis et al, 1992), organizational conflict (Zheng et al, 2019), mistrust or distrust in the organizational setting (O'Boyle & Shilbury, 2016) and the cost of change (Kihl et al, 2010). However, the lack of consideration given to human experience (e.g., change recipients' readiness for change) in the change process is considered to be the primary reason for the failure of many organizational change initiatives (Fahlén & Stenling, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The sport industry is comprised of a multitude of organizations. It is therefore unsurprising that there are conflicts between organizations (1) and that some of these disputes center on the use of trademarks. Efficiency in law means upholding the process of law enforcement with fairness under the rule of law (2).…”
Section: Introductionmentioning
confidence: 99%